2019
DOI: 10.1002/aenm.201803900
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Carbon Spheres and Their Hybrid Nanomaterials in Electrochemical Energy Storage

Abstract: Electrochemical energy storage is of extraordinary importance for fulfilling the utilization of renewable and sustainable energy sources. There is an increasing demand for energy storage devices with high energy and power densities, prolonged stability, safety, and low cost. In the past decade, numerous research efforts have been devoted to achieving these requirements, especially in the design of advanced electrode materials. Hollow carbon spheres (HCS) derived nanomaterials combining the advantages of 3D HCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
149
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(160 citation statements)
references
References 259 publications
1
149
0
Order By: Relevance
“…In this connection, other smaller‐sized templates, such as silica (SiO 2 ) sphere, [ 41,42 ] polystyrene (PS) sphere [ 43 ] and metal powder, [ 30 ] have been widely investigated as potential scaffold for mass production of 3D graphene. Most recently, our group [ 44,45 ] developed a novel CVD‐based synthesis protocol for 3D N‐doped graphene/CdS (NG/CdS) hollow spheres by utilizing SiO 2 spheres and pyridine as the solid template and graphene precursor, respectively. A thin CdS shell was deposited on the surface of SiO 2 followed by a CVD step to allow the in situ growth of a seamless‐contacted NG outer layer.…”
Section: Synthesis Methods Of 3d Graphenementioning
confidence: 99%
“…In this connection, other smaller‐sized templates, such as silica (SiO 2 ) sphere, [ 41,42 ] polystyrene (PS) sphere [ 43 ] and metal powder, [ 30 ] have been widely investigated as potential scaffold for mass production of 3D graphene. Most recently, our group [ 44,45 ] developed a novel CVD‐based synthesis protocol for 3D N‐doped graphene/CdS (NG/CdS) hollow spheres by utilizing SiO 2 spheres and pyridine as the solid template and graphene precursor, respectively. A thin CdS shell was deposited on the surface of SiO 2 followed by a CVD step to allow the in situ growth of a seamless‐contacted NG outer layer.…”
Section: Synthesis Methods Of 3d Graphenementioning
confidence: 99%
“…Note that hollow structures have also been widely used as sulfur hosts for lithium sulfur batteries [27][28][29][30][31]. Several recent articles have reviewed this topic [32][33][34][35]; therefore, they are not covered here.…”
Section: Hscms For Libsmentioning
confidence: 99%
“…Continuous efforts to increase energy density without sacrificing power density and cycle life are still hot topics. [7][8] The macropores not only provide more space for rapid embedding and deintercalation of the active material, but can also be used as an ion buffer container to reduce the diffusion distance of ions in the electrolyte. The abundant pore structure can provide high surface area and electrolyte storage area, which can promote the rapid transfer of electrolyte ions, enrich the buffer channel of ions, and improve the capacity of capacitance and rate.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] It has been reported that micropores can increase the EDLC, while mesopores can reduce the ion transmission resistance. [7][8] The macropores not only provide more space for rapid embedding and deintercalation of the active material, but can also be used as an ion buffer container to reduce the diffusion distance of ions in the electrolyte. [9] Hitherto, a large number of synthetic strategies have been used to make porous carbon materials.…”
Section: Introductionmentioning
confidence: 99%